2021
DOI: 10.1002/htj.22049
|View full text |Cite
|
Sign up to set email alerts
|

Heat and mass transfer of magnetohydrodynamic Casson fluid flow over a wedge with thermal radiation and chemical reaction

Abstract: A numerical computation to analyze the heat and mass transfer mechanism of a magnetohydrodynamic radiative Casson fluid flow over a wedge in the presence of Joule heating, viscous dissipation, and chemical reaction is carried out in this study. The flow‐governing partial differential equations are transformed as ordinary differential equations by relevant similarity transformations and subsequently resolved by Runge–Kutta numerical approach with a shooting technique. The characteristics of momentum, thermal, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Das et al 7 reported temperature‐dependent fluid properties of radiative MHD rarefied slip flow over a wedge surface. Sulochana et al 8 explored the thermosolutal transport phenomenon of Casson fluid flow on a wedge with radiation, Joule heating, chemical reaction, viscous dissipation, and magnetic field. Rashidi et al 9 conducted research on the simultaneous effects on partial and thermal diffusion in stable MHD convection caused by a gyration disc.…”
Section: Introductionmentioning
confidence: 99%
“…Das et al 7 reported temperature‐dependent fluid properties of radiative MHD rarefied slip flow over a wedge surface. Sulochana et al 8 explored the thermosolutal transport phenomenon of Casson fluid flow on a wedge with radiation, Joule heating, chemical reaction, viscous dissipation, and magnetic field. Rashidi et al 9 conducted research on the simultaneous effects on partial and thermal diffusion in stable MHD convection caused by a gyration disc.…”
Section: Introductionmentioning
confidence: 99%
“…It is seen that there is an enhancement in the field of temperature with the radiation, temperature-dependent thermal conductivity, and irregular heat parameters. Sulochana et al, [15] studied Heat and mass transfer of magnetohydrodynamic Casson fluid flow over a wedge with thermal radiation and chemical reaction. They observed that an increase in skin friction values is noted due to an increment in the thermal Grashof number, whereas a decrease is observed due to the chemical reaction parameter.…”
Section: Introductionmentioning
confidence: 99%
“…A chemical reaction among the fluid and the foreign particles takes place in the chemical industrial process. The common examples are the polymer production, the food processing and the manufacture of ceramics or glassware [ 38 ]. Alsaedi et al [ 39 ] analysed the convective thermal transfer of Jeffrey fluid on a stretched surface with chemical reaction.…”
Section: Introductionmentioning
confidence: 99%